(untitled) (Società e diritti, 2019)
In this essay, the Author aim to respond to the urgings in the book “The force of Law” by Frederick Schauer breaking from the paradigm of analytical jurisprudence; insofar as the University of Virginia philosopher states having found sociological bases for his own logical/reconstructive architecture, the Author intend to develop a critique of Schauer’s theses that is not merely theoretical, but sociological as well. In a nutshell whether the use of force is sociologically necessary to control isolated resistance to the rules shared by the majority, or to reinforce a law, that aims to trigger necessary social change, but such a strong limitation of human freedom must be justified; and this legitimacy can only derive from the need for justice. Key words: Justice, natural law, legitimization